ANALISIS MOTIVASI DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL PROVINSI MALUKU - ARIFIN TAPI OYIHOE (Fakultas Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to analyze the effect of work motivation (salary, employment, promotion opportunities, supervision) and organizational climate (responsibility, identity, warmth, support, conflict) on employee performance at the Maluku Provincial Social Service. The research is an explanatory research with data collection done in one step (one shot study) or in cross-section through a questionnaire. Due to the small population, 86 saturated samples were used. Data were analyzed with multiple linear regression.The results showed that (1) work motivation consisting of salary, work itself, promotion, supervision and organizational climate consisting of responsibilities, identity, warmth, support, conflict simultaneously had a positive and significant effect on employee performance, (2) Salary is a variable of work motivation factors that has a positive and significant influence and is most dominant on employee performance and (3) Warmth is a variable of organizational climate factors that has a positive and significant effect and is the second dominant on the performance of employees of the Maluku Provincial Social Service.